Peter Wilkinson PhD - Gill, Philip; Wilkinson, Peter (Cranfield University, 2018)
Properties of Composite Propellants Containing New Elastomeric Binders Traditionally propellants have been made from materials specifically manufactured for this purpose. This project seeks to find whether commercially available thermoplastic elastomers (TPEs) can be used to replace some or all of the existing propellants. Traditionally composite propellants used an inert binder, usually hydroxyl terminated polybutadiene (HTPB), cross linked with an isocyanate and mixed with a powerful oxidiser, normally ammonium perchlorate (AP). It is thought that TPEs may be able to match the excellent mechanical properties and good performance of HTPB propellants, while being much easier to be decommissioned in a more environmentally sound manner. Two TPEs were selected and analysed for suitability as a propellant binder. Inert formulations were created by a new novel process. This involved coating the filler with TPE using a novel slurry coating process involving a Resonant Acoustic Mixer (RAM). The coated mixture was then hot pressed into a slab for mechanical testing.
Keywords: 'PhD'; 'Propellants'; 'Binders'; 'Formulation'; 'Commercial of the Shelf'; 'COTS'; 'Environmental'; 'Chemical Thermodynamics and Energetics'